(untitled) (World Bulletin of Public Health, 2024)
Various dermatological reactions may develop during drug therapy of tumors. Skin toxicity may be accompanied by symptoms such as pain, causing additional suffering to patients; when localized on open areas of the skin, it is perceived by many as an unsightly appearance, which significantly worsens their quality of life. Dermatological reactions are caused by many targeted drugs. Most often, dermatological reactions are caused by epidermal growth factor receptor (EGFR) inhibitors, this is a class effect of all such drugs associated with the inhibition of EGFR physiological signals in the skin. Also, skin toxicity can be caused by a number of antitumor chemotherapy drugs. Alopecia is typical for most cytostatic drugs.